Coverage and capacity modelling analysis for public safety LTE in Singapore - Low, Wei Bin (2018)
This report presents the coverage and capacity modelling analysis for Public Safety LTE (Long Term Evolution) in Singapore with the proposed in-building communication system design. A modelling methodology was used to sketch up the building model. Thereafter, simulation results were generated to provide recommendations on the area of coverage and the number of users the proposed in-building communication system can support.